Incidence of Dysphagia in Patients with Unilateral Vocal Cord Paralysis - Ibrahim Eldsoky (Al-Azhar University, Faculty of Medicine (Damietta), 2021)
Background: It is essential and evaluates dysphagia among patients with UVCP to help the management, improves the quality of life, and prevents secondary complications. Aim of the work: This research aims to find the incidence of dysphagia in patients with unilateral vocal cord paralysis [UVCP]. Patients and Methods: This study was performed in 245 patients with UVCP; 98 males and 147 females. There were two groups of patients: the non-dysphagia group [130 patients] and the dysphagia group [115 patients]. Assessment of patients was performed by the verified 10-item Eating Assessment Tool [EAT-10] and Dysphagia Handicap Index [DHI]. Results: Performing EAT-10 questionnaire revealed average values of 18.5 ± 9.56 and 34.3 ± 11.3 in the non-dysphagia group and dysphagia groups, respectively. DHI showed mean values of 45.7 ± 18.12 and 85.42 ± 21.7 in the non-dysphagia group and dysphagia groups, respectively. All of them demonstrated a highly significant variation [P = 0.001]. Regarding the etiology of UVCP, iatrogenic was the first cause of UVCP; it was the cause of 36.9% and 36.52%, followed by idiopathic; 23.1% and 24.34 %, intubation injury; 12.6% and 11.3%, tumor; 10% and 9.56%, trauma; 8.46% and 8.69%, thyroid surgery; 4.62% and 5.22%, and neurodegenerative disease; 4.62% and 4.35% of non-dysphagia and dysphagia groups, respectively. Conclusion: The incidence of dysphagia in unilateral vocal cord paralysis depends mainly on the cause; however, vocal cord paralysis itself increases the incidence of dysphagia whatever the cause.